"Everything changed!" – the ramification of the Second World War on the Canadian North. Issue 1 (15th November 2019) - Lemelin, Raynald Harvey; Beaulieu, Michel S.; Ratz, David
Abstract : Purpose: The purpose of this paper is to retrace past developments that occurred in the Alaskan and Canadian North as of result of the Second World War and illustrate the ramifications of these events in the Canadian and American political landscapes as it pertains to warfare tourism. The paper also intends to initiate a discussion on how certain narratives pertaining to warfare tourism are promoted, while others are overlooked. Design/methodology/approach: This paper analyses the political, economic, socio-cultural and technological factors that resulted in tourism growth or the lack thereof in the Canadian and American Norths. Findings: Warfare tourism, like most types of tourism, is expected to grow. Through this growth comes opportunities to expand and integrate the discussion pertaining to warfare tourism in the Canadian and American Norths while also providing a starting point for discussion about potential solutions to address warfare tourism and cultural dissonance. Research limitations/implications: This viewpoint is dependent on literature reviews. Practical implications: The relationship between Indigenous peoples and other marginalized populations in the Second World War and warfare tourism is a relatively new research area. For warfare tourism to become integrated into tourism policies and developments, a willingness to address cultural dissonance and integrate populations formerly marginalized in the Second World War will be required. This paper examines how northern and other marginalized voices can be integrated in future commemoration and interpretation strategies. Social implications: The paper provides an opportunity to examine the growth and healing that can result from warfare tourism. Originality/value: This interdisciplinary collaboration conducted by a military historian, a northern historian and a tourism research researcher provides one of the first examinations of the impacts of the Second World War in North America, and the relevance of these impacts to the interpretation of warfare tourism in Canada.